2018
DOI: 10.1038/s41398-018-0260-1
|View full text |Cite
|
Sign up to set email alerts
|

Fasting enhances extinction retention and prevents the return of fear in humans

Abstract: Fear is prone to return following extinction that is the basis of exposure therapy for fear-related disorders. Manipulations that enhance the extinction process can be beneficial for treatment. Animal studies have shown that fasting or caloric restriction can enhance extinction and inhibit the return of fear. The present study examined the effects of fasting on fear acquisition, extinction, and the return of fear in humans. One hundred and twenty-five male participants were randomized into a fasting group and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 65 publications
2
17
0
Order By: Relevance
“…In fear conditioning paradigms, caloric restriction and overnight fasting before extinction training were shown to enhance fear extinction and suppress return of fear in mice (Riddle et al, 2013;Huang et al, 2016;Verma et al, 2016), an effect that was abolished by administration of the GHSR antagonist D-Lys3 into the lateral amygdala (Huang et al, 2016). Interestingly, also in humans spontaneous recovery and reinstatement of fear were reduced after an overnight fast, which was correlated with ghrelin plasma levels (Shi et al, 2018). However, we could not confirm the extinction-promoting effect of overnight fasting using a weak extinction protocol and also found no difference between wild type and GHSR KO mice (Pierre et al, 2020).…”
Section: Effects Of Caloric Restriction On Fear Anxiety-and Depressimentioning
confidence: 93%
See 1 more Smart Citation
“…In fear conditioning paradigms, caloric restriction and overnight fasting before extinction training were shown to enhance fear extinction and suppress return of fear in mice (Riddle et al, 2013;Huang et al, 2016;Verma et al, 2016), an effect that was abolished by administration of the GHSR antagonist D-Lys3 into the lateral amygdala (Huang et al, 2016). Interestingly, also in humans spontaneous recovery and reinstatement of fear were reduced after an overnight fast, which was correlated with ghrelin plasma levels (Shi et al, 2018). However, we could not confirm the extinction-promoting effect of overnight fasting using a weak extinction protocol and also found no difference between wild type and GHSR KO mice (Pierre et al, 2020).…”
Section: Effects Of Caloric Restriction On Fear Anxiety-and Depressimentioning
confidence: 93%
“…To our knowledge, there are currently no studies published that directly investigated the effect of ghrelin-targeted interventions in stress-related psychiatric conditions. One study in healthy human participants found enhanced extinction memory retention and reduced return of fear following an overnight fast, which was negatively correlated with ghrelin plasma levels (Shi et al, 2018). Whether fasting may improve exposure-based psychotherapy outcomes in patients with anxiety disorders or PTSD and whether this would be associated with changes in plasma AG concentrations or brain GHSR function remains to be established.…”
Section: Therapeutic Potential Of Targeting the Ghrelin System In Strmentioning
confidence: 99%
“…This behavioral difference at 0% suggests that components of decisionmaking, such as extinction learning and reward devaluation, may differ in this group. In humans, fasting promotes extinction learning in fear conditioning paradigms, suggesting that food-restriction may enhance extinction learning in our animals, and that this relationship may be dependent on the degree of restriction (Shi et al, 2018). Supporting this, in prior comparisons between weight-based and temporally restricted feeding schedules, animals that were less food restricted (in terms of body weight) were slower to extinguish behavior and subsequently devalue rewards (Baker et al, 2012).…”
Section: Discussionmentioning
confidence: 55%
“…Along this line, activation of CRH neurons in the CeA may facilitate active responses toward external threats and suppress passive freezing behavior . Thus, the fear‐suppressing and extinction‐promoting effects of short‐term fasting, seen in Drosophila , mouse, and healthy human subjects, may be at least in part mediated by activation of specific CeL subpopulations that favors an active coping strategy (Fig. ).…”
Section: Possible Interactions In the Ceamentioning
confidence: 99%
“…Furthermore, the PVH receives afferents from limbic brain areas to integrate emotional stimuli with respective hormonal responses. Hunger promotes fear extinction and the HPA axis is a possible gateway linking hunger and fear. Peripherally released ghrelin activates central arcuate AgRP/NPY neurons and NPY may provide a link to the activation of PVH CRH neurons, triggering the activation of the HPA axis .…”
Section: Closing the Loop––regulation Of The Pvh And Hpa Axismentioning
confidence: 99%